Perspective: Opportunities and Scope for Expanded Deworming Programs for Soil-Transmitted Helminths in India - Aruldas, Kumudha; Khera, Ajay Kumar; Ajjampur, Sitara Swarna Rao (Frontiers in Tropical Diseases, 2021)
The current deworming strategy for soil-transmitted helminthiases (STH) focuses on pre-school and school-aged children and women in the reproductive age to eliminate morbidity. However, mathematical modeling and meta-analysis show that STH could be eliminated if the entire population, including adults, were treated. The Government of India (GOI) has been deworming children through various maternal and child health programs and school health programs. One of the largest initiatives is the school-based biannual deworming program for children aged 1-19 years in the ‘National Deworming Day’ since 2015. Women of the reproductive age have the opportunity to get dewormed under the Anemia Free India program. Adult men and women have the opportunity to receive Albendazole in the lymphatic filariasis (LF) endemic districts. The gaps in deworming are women above the age of 49 and adult men above 19 years, living in non-LF endemic areas. Understanding gaps in deworming will help plan policy changes and program strategies for STH elimination in India, which has 21% of the global STH burden, as well as in other STH endemic countries.